Customer satisfaction towards Al-Hidayah group’s service rental / Nik Hasnita Nik Ismail - Nik Ismail, Nik Hasnita (Faculty of Business and Management, 2009)
A rapidly changing competitive landscape and dynamic customer expectations require construction firms to seek flexibility in product and service development. Product, product quality, keeping delivery commitments, pricing, responsiveness and ability, and communication emerge as effective ways to quickly develop products and services that meets competitive challenges and satisfy customer demands. Product flexibility enables firms to fully explore various product definitions and ideas and allows firms to gather customers’ feedback and investigate design feasibility. Product Quality gains customer trust, provides good service and goods in reasonable price. Responsiveness, ability and good communication among employees produce sales services to satisfy customers. Using data from other construction firms, this research is focuses on customer satisfaction at the in Al-Hidayah Group that relates to products, product quality, pricing, keeping delivery commitments as well as responsiveness and ability, and communication. The Research Methodology used gave a systematic planning required at all stages of the research process. The researcher uses exploratory, descriptive and causal relationships as their research design in conducting the research. The researcher also uses the Systematic Sampling being the most efficient sampling design as their technique. They used telephone and email interviews to collect the data. Customer satisfaction, therefore, becomes a very relevant topic that makes Al-Hidayah Group's research important. According to the findings, the researcher expects that the price is the cause of customer dissatisfaction because the rental price was increase during the economic crisis. But after research complete, researcher found that keeping delivery commitment are the most influence towards Al-Hidayah Group’s service rental and following product or service and product quality.